Paradoks egzystencji etycznej - Galarowicz, Jan (Horyzonty Wychowania, 2017)
Author’s deliberations are concentrated around the widely observedphenomenon of the loss of the basic, in terms of morallife, „ethical paradox” by contemporary man. Following Tischner’sreason, assuming that the source of this oblivion is not the lackof sufficient knowledge of man, but the lack of mutual experiencesof humanity, the author indicates several causes whichled to the degeneration of sensitivity to the paradox of humanethical existence. The author describes it in the context of myth,and at the same time – „being food for thought” – symbol of thedying seed, presenting the axiological ambivalence of life. Death(as one side of this ambivalence) constitutes the „indispensablecondition for participation in the mysterious life” and as such findsits meaning. At the same time, the symbolism of the dying seedbecomes completed in the interpretation of man as a being directed to transcendence, surpassing all egocentrism, geared towards other people. Immanence of human being is broken in the transcending act of the awakening of ethical consciousness and attaining „ethical majority” by man. It consists in „dying for somebody”, choosing self-sacrifice, however going not to the destruction, but to the birth of a new life. Dying is here understood by the author in ethical sense, as getting rid of all the hard and not refined in your heart. Situated in personal „I”, the disinterested power of transcendental ethical smallness as well as a free decision to serve the good according to the „logic of values” enables man – in his own deeds – to accomplish his own self-realization.